Pengukuran Radiasi Kalor pada Beberapa Bohlam yang Berbeda Warna - Nurhayati Nurhayati; Fitra Saputra; Anjar Purba Asmara; Malahayati Malahayati (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2021)
This study aims to compare the rate of heat absorption in black, red, green, yellow, milky white, and blue electrical light related to temperature change with a predetermined time variation. This study uses an AC power circuit to light a bulb with varied colours and then measures the temperature associated with the heat involved in the light on. The calculation in this study uses the Black principle concept. The results showed that black and green light bulbs had the greatest temperature change followed by red, blue, yellow, and white bulbs. This is in accordance with the basic concept that dark colours tend to conduct heat better than bright colours.